MiRNA Regulatory Functions in Photoreceptors - Pawlick, Julia Sophie; Zuzic, Marta; Pasquini, Giovanni; Swiersy, Anka; Busskamp, Volker (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRNAs) are important regulators of gene expression. These small, non-coding RNAs post-transcriptionally silence messenger RNAs (mRNAs) in a sequence-specific manner. In this way, miRNAs take over important regulatory functions, also in the retina. If dysregulated, these molecules are involved in several retinal pathologies. For example, several miRNAs have been linked to essential photoreceptor functions, including light sensitivity and synaptic transmission. Mechanistic miRNA knockout and knockdown studies further linked their functions to degenerative retinal diseases. Of note, the type and timing of genetic manipulation before, during, or after retinal development, is important when studying specific miRNA knockout effects. Within this review, we focus on miR-124 and the miR-183/96/182 cluster, which have assigned functions in photoreceptors in health and disease. We also discuss experimental validation and manipulation of complex miRNA regulatory networks: any given miRNA can target hundreds of mRNAs. Revealing these networks is essential to understand retinal pathologies and to harness miRNAs as precise therapeutic tools to stabilize the photoreceptors’ transcriptomes and, thereby, function.